Business Model and Strategy Development of ABC Groundwater Drilling - Benyamina, Stephanie; Toha, Moh (The Indonesian Journal of Business Administration, 2015)
Abstract – In 2014, economic growth in Indonesia is around 5% while property sector is growing by 10%. Property sector growth is an opportunity for groundwater drilling companies such as ABC Groundwater Drilling since every property needs clean water. It should encounter numerous competitors by offering valuable services to customers. In 2015, ABC Groundwater Drilling is targeting to increase sales revenue and job volume by 40%. Company should creating a lot of improvements to objectify target so that customers would be well perceived the value to be created and delivered through business model canvas development. Purpose of this research is to develop ABC Groundwater Drilling business model and strategy. Conceptual framework is used as a guideline in this research which start from describe problem identification; define research question; analyze current general environment through Resource Based View, PESTEL, Industry Analysis, Business Model Canvas, and SWOT Analysis; conduct Strategy Diamond Model based on research implementation through Analytic Hierarchy Process (AHP) method; formulate appropriate strategy; and implement formulated strategy. Quantitative and qualitative methods are applied in data collection. In-depth interview and survey by using questionnaire are conducted to collect primary data and secondary data is collected from strategic management and related theories. Based on AHP method, ABC Groundwater Drilling should improve  service attribute or criteria continuously to keep performed over competitors. Criteria to be improved by company are after sales service, driller expertise, consulting services, and accuracy. Company should focus on Strategy Diamond Model Analysis which concluded  (i) arena: house development projects outside prime locations in Bandung require clean water; (ii) vehicles: internal development, strategic partnership, internal process improvement, and marketing campaign; (iii) differentiators are after sales service, driller expertise, consulting services, and accuracy; (iv) staging: starts from internal and external training, procedure renewal, job segregation, partnership approach, internal evaluation, and brand strengthening; and (v) economic logic: obtained through developed employee, improved internal process, technology advancement utilization, and expansion. Keywords: Business Model Canvas, Business Strategy, Groundwater Drilling, Strategy Diamond Model